2016
DOI: 10.1038/ng.3517
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequences of Arachis duranensis and Arachis ipaensis, the diploid ancestors of cultivated peanut

Abstract: Cultivated peanut (Arachis hypogaea) is an allotetraploid with closely related subgenomes of a total size of ~2.7 Gb. This makes the assembly of chromosomal pseudomolecules very challenging. As a foundation to understanding the genome of cultivated peanut, we report the genome sequences of its diploid ancestors (Arachis duranensis and Arachis ipaensis). We show that these genomes are similar to cultivated peanut's A and B subgenomes and use them to identify candidate disease resistance genes, to guide tetraplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,006
5
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 767 publications
(1,094 citation statements)
references
References 79 publications
43
1,006
5
10
Order By: Relevance
“…The amplification in all samples using primers designed using sequences from two different species suggested that RS gene family originated before speciation, at least in section Arachis that comprises the samples analyzed. RS gene family has not been studied in wild Arachis, but evidences show peanuts and their wild relatives have many similarities on gene content (Bertioli et al, 2016). Thus, we assume wild Arachis also have a RS gene family.…”
Section: Resultsmentioning
confidence: 99%
“…The amplification in all samples using primers designed using sequences from two different species suggested that RS gene family originated before speciation, at least in section Arachis that comprises the samples analyzed. RS gene family has not been studied in wild Arachis, but evidences show peanuts and their wild relatives have many similarities on gene content (Bertioli et al, 2016). Thus, we assume wild Arachis also have a RS gene family.…”
Section: Resultsmentioning
confidence: 99%
“…Genome sequences for most of the grain legumes are now available, for instance soybean (Schmutz et al, 2010), groundnut progenitors (Bertioli et al, 2016;Chen et al, 2016), chickpea (Varshney et al, 2013d;Parween et al, 2015), pigeonpea (Varshney et al, 2012a), common bean (Schmutz et al, 2014;Yang et al, 2015), and adzuki bean (Kang et al, 2015;Yang et al, 2015) (Table 1). Efforts are underway to sequence the remaining legume genomes.…”
Section: Sequencing and Genotypingmentioning
confidence: 99%
“…It is not likely that one genotype would be significantly better adapted for UV-B rich environments or preferable for UV-B induced trigonelline biosynthesis over any other genotype. This may be due in part to low levels of genetic polymorphism (2.8% on average) between peanut genotypes and similarities with ancestral species [36]. However, trigonelline concentrations increased in all genotypes after irradiation by UV-B.…”
Section: Comparing Stress Responses Across Genotypes and Growth Stagementioning
confidence: 76%